Testing technology to enhance patient safety in seclusion. Issue 1 (13th March 2017) - Johnson, Paula; Evans, David J.W.; Khan, Zulaikha
Abstract : Purpose: The purpose of this paper is to evaluate whether an example of Seclusion Room Contactless Monitoring Technology (VitalGuard TM ) is able to accurately detect the presence of life in a ward seclusion room ensuring patient wellbeing, without interference from background "living noise" (e.g. voices) or "electronic noise" (e.g. other systems). Design/methodology/approach: The authors assessed the system's ability to monitor movement caused by human respiration through its ability to discriminate false positives (i.e. presence of an inanimate object ± movement or noise, in the absence of a person in the seclusion room) and false negatives (i.e. failure to detect a human presence) in a ward setting. Findings: The system displayed 100 per cent validity in terms of determining false positives (six conditions, each n=5) and the system did not alarm under either of the two false negative conditions tested (each n=5). Research limitations/implications: These findings demonstrate that this example of technology is able to monitor movement caused by human respiration and can accurately and reliably detect the presence of life in seclusion rooms, in the ward setting, without interference from background noise (living and electronic). This was a small evaluation study and further research on its effectiveness in practice would be beneficial in both the intellectual disability forensic setting and other settings of segregation and isolation. Originality/value: This study suggests that the use of technology in a seclusion room setting can be used as a reliable tool to enhance patient observations and assist in the delivery of care in a safe and unobtrusive manner.